1988
DOI: 10.1080/08327823.1988.11688044
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Study of 435 MHz Radio-Frequency Radiation on Blood-Borne End Points in Cannulated Rats. Part I: Engineering Considerations

Abstract: To study the effects of exposure to long-term, low-level radio-frequency radiation (RFR) on various physiological systems in a large population of rodents, a complete exposure facility was designed and constructed at the Georgia Institute of Technology. The major components of the facility included a set of circular, stacked, parallel-plate waveguides fed by slotted-cylinder antennas. The waveguides provided a TE10 mode, horizontally polarized field in which the maximal power density occurred midway between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Indeed, no changes were observed in exposed humans for a range of hormones as well, including growth hormone, luteinizing hormone, cortisol, melatonin, and others. Research in rats has shown results consistent with these general findings in that no demonstrable effects on hormones, including melatonin, have been reported with low-level RF exposure at 435 MHz (Bonasera et al, 1988;Toler et al, 1988) or at 900 MHz (Vollrath et al, 1997;Heikkanen and Juutilianen, 1999). Mann et al (1998) reported that pineal and serum melatonin levels were not altered by 6 h exposure to a 900 MHz EMF in rats.…”
Section: Biochemical Changessupporting
confidence: 52%
“…Indeed, no changes were observed in exposed humans for a range of hormones as well, including growth hormone, luteinizing hormone, cortisol, melatonin, and others. Research in rats has shown results consistent with these general findings in that no demonstrable effects on hormones, including melatonin, have been reported with low-level RF exposure at 435 MHz (Bonasera et al, 1988;Toler et al, 1988) or at 900 MHz (Vollrath et al, 1997;Heikkanen and Juutilianen, 1999). Mann et al (1998) reported that pineal and serum melatonin levels were not altered by 6 h exposure to a 900 MHz EMF in rats.…”
Section: Biochemical Changessupporting
confidence: 52%
“…Back reflection from the lateral boundaries of the plates can be 1) ignored [Bonasera et al, 1988], 2) suppressed by tapered resistive wedges at the edge of the guide [Macrakis, 1960], or 3) suppressed by a guidefilling layer of microwave-absorbing foam. We chose the third alternative and employed a ring (ID Џ 0.419 m; OD Џ 0.533 m) of AEL-4.5 foam (Advanced Electro-Magnetics, Santee, CA).…”
Section: Theory Of the Rtlmentioning
confidence: 99%
“…A transverse electromagnetic wave is launched into it by an appropriate radially symmetric antenna at its center; the entire unit is terminated, as appropriate, at the lateral plate boundaries. Such devices have been used biologically [Bonasera et al, 1988]. A World War II technology associated with MIT's Radiation Laboratory [Marcuvitz, 1948[Marcuvitz, , 1951, they are modestly well understood electromagnetically.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, for present studies the exposure system was designed so that the animals could move freely and stay continuously in their cages during and between the exposures where food and drinking water was provided ad libitum. Several RF exposure systems have been developed where animals can freely move in their cages [Guy et al, 1979;Bonasera et al, 1988;Repacholi et al, 1997;Hansen et al, 1999;Wilson et al, 2002]. However, none of these systems seemed to fulfill the requirements of our animal studies as such due to their costs or required space.…”
Section: Introductionmentioning
confidence: 98%